Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Pada Materi Metamorfosis di Kelas IV SD Negeri 1 Tualang Cut - Fatmawati Fatmawati; Ester Julinda Simarmata (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The results of this research indicate an increase in student learning outcomes in metamorphosis material in class IV SDN 1 Tualang Cut. This is proven by the results of research conducted in the first cycle posttest, 14 students (56%) received a complete score, while 12 people (45%) received an incomplete score, with an average learning result of 69.46. In the second cycle posttest, students' complete learning results increased to 24 people (92%) and 2 students (8%) did not complete it, with an average learning result of 90.11. Furthermore, from observing teachers' activities in implementing learning in cycle I, an average of 76.36% was obtained and in cycle II the results of teacher observations increased to 94.54%. Furthermore, from the results of observations of student activities in cycle I, an average of 69.09 was obtained and in cycle II the results of student observations increased to 94.54. The increase in learning outcomes occurred after improvements in actions in cycle II. The action was stopped in cycle II because it had reached the success criteria. Thus, the conclusion was obtained that by implementing the problem based learning model there was an increase in the learning outcomes of metamorphosis material for class IV students at SDN 1 Tualang Cut.